Development of a risk assessment model for the customer performance perspective in power plants applying a system dynamics approach. (6th June 2021) - Mashaqbeh, Sahar Al; Munive-Hernandez, Jose Eduardo; Khazaleh, Awni Al; Khan, M. Khurshid
Risk management is a key management process to identify, understand and assess risks. Customer risks are also relevant to the organisation's long-term strategy and they should also be considered to integrate a robust risk management system. Key risks are not isolated, cause and effect interrelationships can be established among those risks to assess their impact on organisational performance. This situation represents a complex problem. This paper develops a system dynamics (SD) model to assess the impact of customer risks on three key strategic performance measures in power plants (i.e., efficiency, availability, and operational and maintenance costs). The exponential behaviour of customer risks reveals that these risks can be controlled through normal procedures of the risk management process and can be monitored through functional managers and supervisors due to their distribution. The developed model is validated in two power plants in the Middle East through focus group interviews and questionnaire surveys.